Urinary System Manifestation of IgG4-Related Disease: Clinical, Laboratory, Radiological, and Pathological Spectra of a Chinese Single-Centre Study. (3rd July 2020) - Teng, Fei; Lu, Hui; Zheng, Ke; Chen, Gang; Wen, Yubing; Liu, Zheng; Peng, Linyi; Huo, Li; Zeng, Xiaofeng; Zhang, Wen; Li, Xuemei
Abstract : Background . IgG4-related disease is a new disease entity, but little attention was drawn to urinary system involvement besides nephritis or nephropathy. Here, we described clinical, radiological, and pathological manifestations of IgG4-related urinary disease (IgG4-RUD) and assess its treatment responses. Methods . We conducted a retrospective study enrolling 65 IgG4-RUD patients from an IgG4-related disease (IgG4-RD) cohort of the Peking Union Medical College Hospital. Clinical, laboratory, radiological, pathological data were collected, and treatment response to immunosuppressants were analysed. Results . IgG4-related interstitial nephritis (TIN, 32.3%), glomerular nephritis (GN, 7.7%), renal pelvis and ureter involvement (21.5%), abnormal radiology with quiescent clinical presentation (13.8%), and renal parenchymal lesion plus retroperitoneal fibrosis (RPF, 18.5%) were major lesion types of IgG4-RUD. All patients had elevated serum IgG4, 76.9% had hyperglobulinemia, and 92.3% had elevated serum IgE at diagnosis. IgG4-TIN patients presented with renal dysfunction, and 94.3% had low serum complement C3 and IgG4-GN presented with nephrotic syndrome, while renal pelvis and ureter involvement had normal renal function and urinalysis. IgG4-RPF with renal parenchymal involvement presented with acute renal dysfunction and required emergency medical intervention. Renal cortex low-density areas, parenchyma or pelvis nodular mass, bilateral enlargement of the kidney, and renal pelvis and ureter mass/wall thickening were specific image patterns of IgG4-RUD. Infiltration of plasma lymphocytes and storiform fibrosis were histopathological features of IgG4-RUD. Patients showed satisfactory responses to immunosuppressive treatment, but complete recovery of renal function was difficult to achieve in IgG4-TIN. Four patients (6.2%) experienced clinical relapses during the maintenance period. Conclusion . IgG4-RUD had diverse lesion types and distinctive manifestations. Radiological examinations were helpful for diagnosis and treatment evaluation. Patients showed good initial response to immunosuppressive treatment but relapses could occur at the maintenance period.